Effect of Transformational Leadership on the Creativity of Employees: An Empirical Investigation - Teymournejad, K.; Elghaei, R. (Engineering, Technology & Applied Science Research, 2017)
Considering the accelerated pace of developments and advancements in the current era, organizations which have innovative, change-oriented managers and leaders with a long-term vision are more likely to survive the competitive environment. Undoubtedly, leadership behavior and style considering creativity and innovativeness of employees within the organization as an incentive of organizational change considerably influence employee needs and knowledge. The purpose of this study is to determine the effect of transformational leadership involving idealized influence, intellectual stimulation, inspirational motivation and individualized considerations on organizational creativity of employees in the Maskan Bank in Tehran. This study is an applied research using descriptive data analysis. Data is collected by questionnaires. Correlation is used to analyze the hypotheses. The studied population includes all managers and employees of the Maskan Bank in Tehran Province. Using Cochran formula, 127 employees are selected as a sample. Validity and reliability of the questionnaire are calculated by using expert opinion and Cronbach Alpha. The normal distribution of variables is determined by using Kolmogorov-Smirnov test and confirmatory factor analysis; hypotheses are tested by using linear structured relationships. All hypotheses are confirmed; that is, transformational leadership as a whole and each of its dimensions, such as idealized influence, intellectual stimulation, individualized consideration and inspirational motivation have a significant and positive effect on creativity of Maskan Bank employees.